Effective ICTs in agricultural value chains to improve food security: An international perspective - Armstrong, L.; Diepeveen, Dean; Gandhi, N. (2011)
This paper examines the grains value chain in agriculture, and identifies the importance in developing strategies which could better secure food production. The study highlights examples of successful integration of ICTs in agricultural supply and value chains. The development of strategies to integrate these ICTs into the supply chain will be proposed. It will be argued that the use of high powered computing for data mining and other technologies such as sensor networks, mobile communications, and GPS technologies can revolutionize the efficiency of these supply chains and therefore improve the food security. The study carried out a situational analysis of agricultural resources using standard internet search engines and applying data mining techniques in order to demonstrate how such technologies can be used to show difference in value chains across different situations. An assessment of the study found that the results from the grain-industry dataset support the similar supply chain grouping reported for other research studies. These groupings reflect the more-developed food-industry supply chains and may not capture all the interactions in less-developed supply chains. For example, when several of the food production processes are carried out by one food-producer, the activities will be more difficult to identify. © 2011 IEEE.